2016
DOI: 10.5935/abc.20160063
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Smoking Consumption and Nicotine Dependence Degree in Cardiac Autonomic Modulation

Abstract: BackgroundSmoking consumption alters cardiac autonomic function.ObjectiveAssess the influence of the intensity of smoking and the nicotine dependence degree in cardiac autonomic modulation evaluated through index of heart rate variability (HRV).Methods83 smokers, of both genders, between 50 and 70 years of age and with normal lung function were divided according to the intensity of smoking consumption (moderate and severe) and the nicotine dependency degree (mild, moderate and severe). The indexes of HRV were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
1
3
0
2
Order By: Relevance
“…13,14,52-54 Bodin et al, 52 avaliaram fumantes em períodos durante os quais eles consumiram e não consumiram cigarros por 12 horas, e observaram que, depois de fumar, os participantes apresentaram redução de VFC, com uma redução de HF e intervalos de RR quando comparados a períodos em que não fumaram. Em fumantes pesados, Santos et al, 14 observaram aumento de índice de LF (un) e de LF/HF, e a diminuição do índice HF (un) e da razão SD1/SD2, em comparação com fumantes moderados.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…13,14,52-54 Bodin et al, 52 avaliaram fumantes em períodos durante os quais eles consumiram e não consumiram cigarros por 12 horas, e observaram que, depois de fumar, os participantes apresentaram redução de VFC, com uma redução de HF e intervalos de RR quando comparados a períodos em que não fumaram. Em fumantes pesados, Santos et al, 14 observaram aumento de índice de LF (un) e de LF/HF, e a diminuição do índice HF (un) e da razão SD1/SD2, em comparação com fumantes moderados.…”
Section: Discussionunclassified
“…Essas alterações produzem a diminuição da frequência cardíaca e o aumento da variabilidade de frequência cardíaca (VFC). 11,12 Fumantes apresentam alterações no SNA caracterizadas por reduções de modulação parassimpática, 13,14 o que sugere que, além de os fumantes apresentarem distúrbios do sono devido ao consumo de cigarros, a redução da modulação parassimpática nesses indivíduos também pode afetar a qualidade do sono.…”
Section: Introductionunclassified
“…In addition, recent research has shown that smokers have decreased heart rate variability (HRV), which could be related to increased depression [9][10][11][12][13] . HRV refers to the natural variation of the frequency, that is, the difference in the interval between successive cardiac contractions 14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…I have read, with great interest, the article entitled "Influence of Smoking Consumption and Nicotine Dependence Degree in Cardiac Autonomic Modulation" by Santos et al., 1 recently published in Arquivos Brasileiros de Cardiologia 2016; 106: 510-8. The reseearchers reported that only the intensity of smoking consumption had influences over cardiac autonomic modulation of the evaluated smokers.…”
mentioning
confidence: 99%
“…Smokers with severe smoking consumption intensity presented worse autonomic modulation than moderate ones. 1 …”
mentioning
confidence: 99%